(untitled) (Proceedings of the International Conference on Future of Women, 2018)
The mid-19th century proved a prime time for the question of women’s equality in the U.S., that was voiced by many scholarly fields as diverse as history, anthropology, sociology, gender studies, literature, etc.,and particularly the American novel—The Scarlet Letter; Little Women; The Portrait of a Lady; The Awakening, and Sister Carrie. These novels through their multi-faceted and lifelike protagonists systematically instituted the base of American feminism atits different evolutionary phases. The study explores how these five mid-19th century American novels dealt with the issue of women’s equality through the lenses of New Historicism and Gender Studies. Through close socio-historical readings of these novels, I will discuss how struggle for women’s rights was presented in the select novels, how closely these depictions are aligned with actual social conditions, and how the novels facilitated a social change regarding woman’s equality. Finally the study signifies how the experience can augment the cause of contemporary Pashtun women’s rights in Pakistan, which is a burning issue at the moment.